MAIZE HYBREDS REACTION TO Curvularia ssp, UNDER TWO LEVELS OF NITROGEN FERTILIZATION, IN THE SOUTH TOCANTINS STATE, BRAZIL - VAZ-DE-MELO, Aurélio; AFFÉRRI, Flávio Sérgio; DOTTO, Michel Antonio; PELUZIO, Joenes Mucci; SANTOS, Gil Rodrigues dos; CARVALHO, Edmar Vinicius de (Scientia Agraria, 2010)
The present study aimed to evaluate the resistance of plants of twenty and three maize hybrids to Curvularia spp, the ethiologic agent of Curvularia leaf spot and to evaluate the best timing to assess under conditions of natural infection and two levels of nitrogen and the effect of the pathogen in the productivity, in South of Tocantins State, Brazil. The experiments were conducted at the Experimental Station, Campus Gurupi, of the Federal University of Tocantins - UFT. The severity of the disease was evaluated in two seasons, in the flowering and 30 days after flowering. On average the reaction of the hybrids to concern the severity of the Curvularia leaf spot was higher in the second evaluation. However, the higher dose of nitrogen was greater genetic variance. The XGN5320 hybrid had the highest note of severity (80%), being that, different from other hybrids. The reaction of the maize hybrids UFT-11x52, 127x12, 127x52, 82x38, 8x52 and 8x111, with respect to the Curvularia leaf spot are not dependent on nitrogen levels. The maize hybrids more resistant to Curvularia leaf spot are UFT - 111x1149, 12x11, 12x38 and 8x12.